The role of concomitant alcohol and drug use in increased risk for burn mortality outcomes. Issue 1 (February 2020) - Govender, Rajen; Hornsby, Nancy; Kimemia, David; Van Niekerk, Ashley
Highlights: The risk for mortality was increased when burn injuries were partial and full thickness burn degree and TBSA was more than 30%. Patients with concomitant drug and alcohol use had a 10 times increased risk for mortality compared to morbidity. Increased length of hospital stay diminished the risk for mortality by 10%. Abstract: Background: Burn injuries are a major cause of mortality and morbidity in low- and middle-income countries, with high rates in Sub-Saharan Africa. The risks may be heightened for persons who present with concomitant use of alcohol and illicit substances, which increase the risk for injury and severely compromise prognosis following injury. Methods: This study utilised a national dataset on hospitalised burns in South Africa to explore the risk for mortality relative to morbidity. To assess the influence of alcohol and drugs in mortality outcomes, the analysis was restricted to adult cases, 18 years and older (N = 918). The primary statistical procedures used in the analysis were logistic regression models. Findings: The results indicate that burn victims with full thickness and partial thickness burn degree and more than 30% TBSA had a significantly increased risk of mortality. In addition, the risk for mortality was increased ten times when concomitant alcohol and drugs were indicated compared to cases where these were absent. The length of stay in hospital diminished the risk for mortality by about 10%. Interpretation: The findings may be explained by the role of skin as the main barrier against infections and the concurrent increase in risk of infection based on the degree and extent of any damage. The combined presence of both alcohol and drugs may predispose towards more severe burns and greatly compromise liver function with heightened risk for sepsis and death.